2013
DOI: 10.1093/cercor/bht315
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Television Viewing on Brain Structures: Cross-Sectional and Longitudinal Analyses

Abstract: Television (TV) viewing is known to affect children's verbal abilities and other physical, cognitive, and emotional development in psychological studies. However, the brain structural development associated with TV viewing has never been investigated. Here we examined cross-sectional correlations between the duration of TV viewing and regional gray/white matter volume (rGMV/rWMV) among 133 boys and 143 girls as well as correlations between the duration of TV viewing and longitudinal changes that occurred a few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 55 publications
5
80
1
3
Order By: Relevance
“…Although we have gathered the data of the Child Behavior Checklist, we have not excluded the subjects based on the score of this test in this project (Taki et al, 2010(Taki et al, , 2012aTakeuchi et al, 2013c), which is consistent with studies reported by some of other groups considered leading experts in the field (Kadosh et al, 2013;Sucksmith et al, 2013;Ullman et al, 2014). This is partly because this criterion would exclude many subjects who do not suffer from their problems so much that they do not feel the necessity to visit a hospital for their cure.…”
Section: Methodssupporting
confidence: 68%
“…Although we have gathered the data of the Child Behavior Checklist, we have not excluded the subjects based on the score of this test in this project (Taki et al, 2010(Taki et al, , 2012aTakeuchi et al, 2013c), which is consistent with studies reported by some of other groups considered leading experts in the field (Kadosh et al, 2013;Sucksmith et al, 2013;Ullman et al, 2014). This is partly because this criterion would exclude many subjects who do not suffer from their problems so much that they do not feel the necessity to visit a hospital for their cure.…”
Section: Methodssupporting
confidence: 68%
“…7, 8, 9 A similar tendency between the amount of VGP and regional gray matter volume in the left dorsolateral PFC (T =3.27, 689 mm 3 , P <0.0025) was observed in the cross-sectional analysis of this study. In that analysis, VBM analysis was performed using the same covariates used in this study (for details of methods of preprocessing, see Takeuchi et al 26 ). However, additional studies have indicated that the increased gray matter related to computer experience in children and young adults exerts negative psychological consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional whole-brain multiple regression analysis was performed to investigate the association between MD or FA and the amount of VGP. The covariates were the same as those used in the psychological cross-sectional analyses, except that in imaging analyses, the total intracranial volume calculated using voxel-based morphometry (for details, see Takeuchi et al 26 ) was added as a covariate.…”
Section: Methodsmentioning
confidence: 99%
“…While a few cross-sectional studies and fewer longitudinal studies suggest adverse effects, others suggest media has a beneficial effect on neuropsychological development 9, 10. Such inconsistency can be partly attributed to different methodologies applied by these studies.…”
Section: Introductionmentioning
confidence: 99%